Inhibition of Oral Pathogenic Bacteria, Suppression of Bacterial Adhesion and Invasion on Human Squamous Carcinoma Cell Line (HSC-4 Cells), and Antioxidant Activity of Plant Extracts from Acanthaceae Family - Sureeporn Suriyaprom; Pornpimon Ngamsaard; Varachaya Intachaisri; Nitsanat Cheepchirasuk; Aussara Panya; Thida Kaewkod; Yingmanee Tragoolpua (Plants, 2024)
Medicinal plants have traditionally been used to treat various human diseases worldwide. In this study, we evaluated the leaf extracts of plants from the Acanthaceae family, specifically Clinacanthus nutans (Burm.f.) Lindau, Thunbergia laurifolia Lindl., and Acanthus ebracteatus Vahl., for their compounds and antioxidant activity. The ethanolic extracts of A. ebracteatus showed the highest total phenolic content at 22.55 mg GAE/g extract and the strongest antioxidant activities, with IC50 values of 0.24 mg/mL and 3.05 mg/mL, as determined by DPPH and ABTS assays. The antibacterial efficacy of these extracts was also tested against Streptococcus pyogenes, Streptococcus mutans, Staphylococcus aureus, and Klebsiella pneumoniae. The diameters of the inhibition zones ranged from 14.7 to 17.3 mm using the agar well diffusion method, with MIC and MBC values ranging from 7.81 to 250 mg/mL. Anti-biofilm formation, antibacterial adhesion, and antibacterial invasion assays further demonstrated that these medicinal plant extracts can inhibit bacterial biofilm formation and prevent the adhesion and invasion of oral pathogenic bacteria on the human tongue squamous cell carcinoma-derived cell line (HSC-4 cells). The ethanolic extracts of C. nutans and A. ebracteatus were able to inhibit the gtfD and gbp genes, which facilitate biofilm formation and bacterial adherence to surfaces. These findings provide new insights into the antibacterial and antioxidant properties of plant extracts from the Acanthaceae family. These activities could enhance the clinical and pharmaceutical applications of plant extracts as an alternative therapy for bacterial infections and a dietary supplement.